Pour une Approche Sémantique du Titre - Noui, Siham Noui, Siham; Khennour, Salah Salah, Khennour (جامعة قاصدي مرباح - ورقلة, 2018)
تتخطى الكتابات الأكاديمية بأشكالها المختلفة مجال الكتابة المعتادة إلى الكتابة الكبرى مثل علم القياس. هذا العلم الذي يختلف من نص أكاديمي إلى آخر، هو مساهمة في الدراسة الدلالية لعناوين المقالات الأكاديمية. كما تتضمن هذه الأخيرة في صياغتها مستويات متعددة من التحليل لتحقيق المعنى المقصود في صيغة واضحة. ومن بينها المستوى الدلالي، الذي تطرقنا لدراسته خلال عملنا هذا.
Academic writing in their different forms goes beyond the field of the normal writing to the larger ones such as meteorology. This science which differ from one academic text to another, contributes in the semantic study of the title of the scientific articles. The writers of academic writing, in their elaboration of titles involve several levels of analysis to achieve the intended meaning in a clear formulation. Among these, we choose the semantic level, which we are going to dealt with in our stud.
Keywords: المقالات الأكاديمية -- علم الدلالة -- السيميائية